Developing the Islamic Religious Education Curriculum in Inclusive Schools or Madrasah and Its Implementation: A Systematic Literature Review - Arbain Nurdin; Hendra; Khozin; Abdul Haris; Nurul Zainab; Mohammad Zaini Yahaya (Jurnal Pendidikan Agama Islam, 2024)
Purpose – This research aims to obtain information about the development and implementation of Islamic religious education curricula in inclusive schools or madrasas. An inclusive school or madrasah is an educational institution that provides opportunities for all students, including students with special needs, to study together with the help of accompanying teachers. Design/methods/approach – This study used a systematic literature review of accredited articles from 2018-2023, data collected from Google Scholar, the Science and Technology Index of the Ministry of Education, Culture, Research and Technology of the Republic of Indonesia, and Scopus. Descriptive analysis techniques were used as data analysis techniques. The researcher obtained 120 articles, which further extracted and coded them using the NVivo application, and then found 25 articles that met the TAPUPAS criteria and were relevant to the research question. Findings – Based on the results of the analysis and literature review, some conclusions have been drawn. First, developing an inclusive Islamic religious education curriculum in schools or madrasas has been adjusted to the character of students with special needs and the simplification of subject matter. Meanwhile, the obstacle for Islamic teachers in developing the curriculum is the lack of knowledge to identify students with special needs and limited learning resources and media about it. Second, the implementation is in the form of the application of individual approaches, varied models and methods that have an impact on the effectiveness of learning, and visual media and assessment techniques based on basic abilities for students with special needs in inclusive schools or madrasas. Research implications/limitations – The results of this study still have limitations in the number of articles analyzed and reviewed, especially those published in Sinta 1 accredited journals. Originality/value – This study can be used as a reference for future research, which is expected to provide a more comprehensive study so that the research findings can be improved or perfect.